Application of droplet digital PCR to detect the pathogens of infectious diseases. Issue 6 (16th November 2018) - Li, Haiyi; Bai, Ruolan; Zhao, Zhenyu; Tao, Lvyan; Ma, Mingbiao; Ji, Zhenhua; Jian, Miaomiao; Ding, Zhe; Dai, Xiting; Bao, Fukai; Liu, Aihua
Abstract : Polymerase chain reaction (PCR) is a molecular biology technique used to multiply certain deoxyribonucleic acid (DNA) fragments. It is a common and indispensable technique that has been applied in many areas, especially in clinical laboratories. The third generation of polymerase chain reaction, droplet digital polymerase chain reaction (ddPCR), is a biotechnological refinement of conventional polymerase chain reaction methods that can be used to directly quantify and clonally amplify DNA. Droplet digital polymerase chain reaction is now widely used in low-abundance nucleic acid detection and is useful in diagnosis of infectious diseases. Here, we summarized the potential advantages of droplet digital polymerase chain reaction in clinical diagnosis of infectious diseases, including viral diseases, bacterial diseases and parasite infections, concluded that ddPCR provides a more sensitive, accurate, and reproducible detection of low-abundance pathogens and may be a better choice than quantitative polymerase chain reaction for clinical applications in the future.